Deep indexing and the application of metadata to supplemental materials in journal publishing - Rodríguez-Yunta, Luis (Anuario ThinkEPI, 2014)
Among the best practices of academic journals publishing, this note focusses on the NISO recommendation about the inclusion of supplemental materials. The paper justifies the need to give special treatment to these materials, which require specific metadata. Finally it relates these practices with the deep indexing trend among bibliographic database producers such as ProQuest.
Keywords: Academic journals; Graphic material; Databases; Deep indexing; Metadata.